Is use of the human papillomavirus vaccine among female college students related to human papillomavirus knowledge and risk perception?. Issue 1 (19th October 2009) - Licht, Andrea S; Murphy, Jill M; Hyland, Andrew J; Fix, Brian V; Hawk, Larry W; Mahoney, Martin C
Abstract : Background: Few studies have examined factors associated with the actual use of the human papillomavirus (HPV) vaccine since licensure in 2006. The aims of this study were to assess HPV vaccination rates and to examine whether knowledge and risk perceptions regarding HPV were associated with the reported use of the HPV vaccine among female college students. Methods: Using a cross-sectional design, 406 women aged 18–26 years were recruited at two public universities and completed a self-administered survey. Respondents who reported having received at least one dose of HPV vaccine were classified as 'vaccinated' (n=177, 43.6%). Responses, stratified by the receipt of HPV vaccine, were compared using descriptive statistics and multivariate models. Results: Based on multivariate logistic regression modelling, 18-year-old women were approximately four times more likely to report use of the HPV vaccine compared with respondents aged 19–26 years. Respondents who correctly indicated that HPV caused genital warts were 1.85 times more likely (adjusted odds ratio (OR) 1.85, 95% CI 1.20 to 2.93) to have received at least one HPV vaccine. African American and Asian women were each less likely to be vaccinated compared with white women. Risk perception was not significantly associated with vaccine uptake, however, the majority of respondents failed accurately to recognise their high risk of both acquiring and transmitting HPV. Conclusions: These findings suggest knowledge deficits and misperceptions about HPV risk as potential themes for educational campaigns encouraging the greater use of the preventive HPV vaccine among this subgroup.